2021
DOI: 10.1080/00036846.2021.1946476
|View full text |Cite
|
Sign up to set email alerts
|

Insider share pledging and firm value consequences under the COVID-19: evidence from China

Abstract: Share pledging, the practice in which shareholders secure a loan using their shares, has become a global phenomenon in recent years. In this paper, we investigate the effect of such corporate insider actions on outsider wealth during the pandemic. Concretely, we examine how firms' market value change when corporate insiders pledge their shareholdings during China's COVID-19 outbreak. It is found that market investors responded adversely to share pledging announcements by firms in the high pandemic-affected reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Investors often have negative expectations for the firms’ experiencing huge stock shocks. According to Xiao et al [ 47 ], market investors are more pessimistic about share pledging during challenging periods. For example, pledged shares’ mandatory liquidation triggered by the 2015 Chinese stock market crisis led to a stock price crash due to investors’ irrational behavior [ 34 ].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Investors often have negative expectations for the firms’ experiencing huge stock shocks. According to Xiao et al [ 47 ], market investors are more pessimistic about share pledging during challenging periods. For example, pledged shares’ mandatory liquidation triggered by the 2015 Chinese stock market crisis led to a stock price crash due to investors’ irrational behavior [ 34 ].…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…The share pledging market experienced fast growth following a regulation on the approval of share pledge repurchase transactions which was issued on 24th May 2013 by Shanghai Stock Exchange, Shenzhen Stock Exchange and China Securities Depository and Clearing Corporation (Xiao et al , 2021). The standardization of share pledge repurchase transactions simplifies the process of share pledge and lowers the financing costs and therefore motivates shareholders to use share pledge as one of their major financing channels.…”
Section: Share Pledging In Chinamentioning
confidence: 99%
“…5.3.3 Difference-in-difference analysis. As explained earlier, the 2013 regulation on the approval of share pledge repurchase transactions simplified the process of share pledging and reduced financing costs (Xiao et al, 2021). The 2013 regulation provides shareholders with stronger incentives to use share pledge as one of their major financing channels.…”
Section: Evidence From Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this argument, the prior literature has shown that controlling shareholders' share pledging can induce expropriation behaviors, such as tunneling resources from firms (Kao et al, 2004), and have negative effects on shareholder wealth (Dou et al, 2019). In the specific setting of COVID‐19, Xiao et al (2021) showed that share pledging had a negative impact on firm value in the highly pandemic‐affected regions in China. Some studies provide evidence of the negative association between share pledging and innovation input, measured by research and development (R&D), and innovation output, measured by patents granted (Pang & Wang, 2020; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%